The Strategic Role of Curriculum in the Transformation of Islamic Education - Mujib, Muhammad Farhan; Ma'shum, Firdaus Asrori; Nursikin, Mukh (Al-Mudarris, 2025)
Education cannot be separated from the curriculum. Every educational institution will certainly use the curriculum as a reference to achieve the desired goals. The curriculum as the main component in the educational process, plays a vital role in developing the potential of students, both morally, intellectually, and skills. The purpose of this paper is to find out how the role of the curriculum in the transformation of Islamic education. The method used in the study is the library research method. The sources used in this study came from books, journal articles, and other literature related to the research topic. The results of the study show that in Islamic education, the curriculum has three main roles, namely conservative to preserve cultural and religious values, creative to create innovations according to the times, and critical and evaluative to adjust values ​​to the modern context. The function of the curriculum is discussed in various aspects, including students, educators, madrasah principals, parents, educational institutions, and the community. The importance of cooperation between educational stakeholders to create a curriculum that is flexible, futuristic, and adaptive to changes in the times. By strengthening a harmonious and optimally functioning curriculum, Islamic education can produce competent individuals who are able to adapt to the progress of the times and build a more harmonious, just, and sustainable society. The ideal curriculum must be harmonious, function optimally, and involve cooperation between various parties in the world of education.